Size Management and Cost Stickiness On Rural Banks - Johan, Ardilla Mahardhika; Prabowo, Ronny (Jurnal Keuangan dan Perbankan, 2023)
This study examines the effect of a managerial incentive on the cost behavior of rural banks (BPR or Bank Perkreditan Rakyat) as a consequence of the enactment of FSA-R 5/2015. This study hypothesizes that rural banks with core capital less than IDR 3 billion will exhibit higher anti-sticky cost behavior. The regression analysis of a sample of 242 rural banks in Central Java Province in 2015-2019 empirically demonstrates evidence that rural banks with core capital less than IDR 3 billion reduce more costs when sales decline than those with core capital above IDR 3 billion, implying that these rural banks exhibit greater anti-sticky cost behavior. This cost behavior is motivated by a managerial incentive to increase their core capital by engaging in size management. This study also documents that rural banks with core capital below IDR 3 billion exhibit the highest anti-sticky cost behavior in 2015, when the regulation was initially implemented. Overall, this study underscores the importance of size management incentives in explaining firms' cost behavior.  DOI:10.26905/jkdp.v27i4.9909